Aerobic exercise improves cardiac autonomic modulation in women with polycystic ovary syndrome. (1st January 2016) - Sá, Joceline C.F.; Costa, Eduardo C.; da Silva, Ester; Tamburús, Nayara Y.; Porta, Alberto; Medeiros, Leany F.; Lemos, Telma M.A.M.; Soares, Elvira M.M.; Azevedo, George D.
Abstract: Background: This study aimed to evaluate the effects of aerobic exercise on cardiac autonomic modulation in women with polycystic ovary syndrome (PCOS). Methods: Thirty women with PCOS (25.8 ± 4.8 years old; body mass index, BMI ≥ 25 kg/m 2 ) were divided into two groups; exercise group (n = 15) and control group (n = 15). R–R interval was recorded during 15-min at rest in the supine position. Heart rate variability (HRV) was analyzed by linear (rMSSD, SDNN, LF, HF, LFnu, HFnu, and LF/HF) and nonlinear methods (Shannon entropy, SE; symbolic analyses, 0 V%, 1 V%, 2LV%, and 2UV%) at baseline and after 16 weeks. The multivariate analysis of covariance was used to analyze the effects of exercise on HRV indexes, adjusted for changes in BMI, fasting insulin, and testosterone level. Results: The exercise group increased parasympathetic modulation (rMSSD, HF, HFnu, 2UV%; (p < 0.05)) and decreased sympathetic modulation (LF, LFnu, 0 V%; (p < 0.05)) independently of changes in BMI, fasting insulin, and testosterone level. Moreover, the exercise group decreased resting HR and systolic blood pressure (p < 0.05). All parameters remained unchanged in the control group. Conclusions: Aerobic exercise increased vagal modulation and decreased sympathetic modulation in women with PCOS. This finding reinforces the recommendations for exercise during the clinical management of these patients.